Rekrutmen Calon Anggota Legislatif untuk DPRD Provinsi Jawa Tengah Pada Pemilu 2014 (Studi di DPD Partai Golkar Jawa Tengah) - Maria Ayu Nugraheni; Fitriyah .; Nunik Retno H (Journal of Politic and Government Studies, 2014)
This study was conducted to clarify how the Golkar Party Central Java Province recruiting for candidates for the legislature. Current open election system, the role of the party had no candidate winning by voting against the party or parties who determine who will enter the cadres in the government but the people who determine which candidates will advance in the parliament as representatives of the people. The emergence of new questions that with this system, the opportunity for political influence money can happen. In fact, this system is expected to function in the recruitment party should further clarified that produced a cadre of qualified cadres. In addition, the Golkar Party declared himself as a modern party which means that the party is ready to change the political climate in Indonesia with a cadre of candidates while maintaining electability. Then how is the role of Local Councils Golkar Party Central Java province in recruiting candidates in the 2014 election? Is the background of the party choose Golkar cadres and how to prepare the candidate as well as the constraints that occur when such recruitment.This study used qualitative research methods, in which researcherscollected data is written and spoken words of research subjects and informants.Field data obtained by conducting in-depth interviews and the literature.These results indicate that the Golkar Party is a modern party that is stilldoing the traditional system in recruiting legislative candidates. List ofCandidates Golkar Party in Central Java is cadres who have entered more than 5years with a minimum education requirement bachelor's. In addition, the TeamSelection still use personal ties and money to be able to enter candidates. Toassist the winning votes for the candidates, the Local Councils will deploy itsability to build a network in each electoral district Local Councils to helpalthough in practice, it is known that sometimes struggles to win the mountingarea in each electoral district and still be one of the obstacles that occur for thecandidates.Keywords: Recruitment, Legislative Candidates, Regional Parlement of CentralJava, Golkar Party